Speech genres of electronic communication between lecturer and student - Prom, Natalia Aleksandrovna; Evtushenko, Oksana Aleksandrovna; Shestakova, Olga Александровна (Жанры речи)
The article presents analysis of the genre repertoire of electronic communication between a lecturer and a student, as one of the new areas of Internet communication, which has not been the subject of linguistic and genre analysis. The article offers and substantiates a classification of identified speech genres. The relevance of the topic is determined by the fact that this business form of communication is becoming preferable in modern pedagogical discourse due to numerous social and technological processes. The research material consists of written electronic asynchronous communication texts between lecturers and students in a computer-mediated environment. Using the methods of observation and comparison of various genres formed in the process of electronic communication, we have created the author’s speech genres classification relevant for modern electronic communication between a lecturer and a student. This classification includes informative, etiquette, imperative and evaluative groups of genres. In a quantitative sense, informative and etiquette genres significantly predominate over imperative and evaluative ones. The group of informative genres has been found to be the largest in our empirical material, which is due to the goals and objectives of this type of communication – providing and requesting information. The large number of etiquette speech genres indicates that the etiquette norms of institutional communication are followed due to their significance. Imperative and evaluative genres are included in the lectures’ speech repertoire, which is caused by the institutional nature of the considered form of interaction. The identified speech genres have a number of characteristics: secondary, written and formal and they possess signs of oral informal speech of primary genres, which allows us to assert that electronic communication between a lecturer and a student is going through a stage of formation and development.